In silico quantitative structure pharmacokinetic relationship modeling of quinolones: Apparent volume of distribution - Paul, Yash; Dhake, Avinash S; Dhake, Avinash S; Singh, Bhupinder; Singh, Bhupinder (Asian Journal of Pharmaceutics (AJP), 2014)
The use of in silico approaches for successful prediction of pharmacokinetic properties of compounds during new drug discovery has been increasing exponentially. These in silico models, for the prognosis of absorption, distribution, metabolism and excretion (ADME), are invariably based on the implementation of quantitative structure pharmacokinetic relationship (QSPR) techniques. The current study was conducted to investigate QSPR for apparent volume of distribution (Vd) in man among 24 Quinolone drugs employing an extrathermodynamic approach. It is vital to predict the Vd value of various drug leads during drug discovery so that compounds with poor bioavailability can be eliminated and those with an acceptable metabolic stability can be identified. Analysis of several thousands of QSPR correlations developed in the present study revealed an extremely high degree of cross-validated coefficient (Q2) using the leave-one-out method (P < 0.001). Logarithmic transformation tends to improve the correlations marginally (R2 = 0.936) but the inverse transform resulted in a distinct improvement in the correlation (R2 = 0.994). Electronic and topological parameters were found to primarily ascribe the variation in Vd. Overall, the diffusional interactions seem to play a major role in attributing Vd rather than the permeational ones.